2020
DOI: 10.1021/acs.iecr.9b06951
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Long-Chain n-Alcohols to Linear α-Olefins Using Sodium-Modified γ-Al2O3

Abstract: Linear α-olefins (C8–C12 α-olefin, LAOs) are acknowledged as high-value-added chemicals in both lubricant production and the polyolefin industry. An alternative route to the synthesis of high-purity LAOs is the dehydration of linear long-chain n-alcohols, whereas elevating the activity and selectivity of catalysts remains a challenge. Herein, we presented that on using sodium-modified γ-Al2O3 as the catalyst, a high selectivity (up to 96.87%) to 1-decene was achieved, and an optimized experimental condition (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The linear alpha olefins (LAOs), linear hydrocarbons with a C=C bond at the terminal position, are chemical intermediates attractive for use in detergents, specialty chemicals, synthetic oils, premium synthetic lubricants and plasticizers, as well as in copolymers [1][2][3][4]. Until now, ethylene oligomerization for homogeneous transition-metal catalysis has been a significant process for LAO production [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The linear alpha olefins (LAOs), linear hydrocarbons with a C=C bond at the terminal position, are chemical intermediates attractive for use in detergents, specialty chemicals, synthetic oils, premium synthetic lubricants and plasticizers, as well as in copolymers [1][2][3][4]. Until now, ethylene oligomerization for homogeneous transition-metal catalysis has been a significant process for LAO production [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the dehydration reaction of fatty alcohol progresses through the synergistic catalysis of acid–base pairs on the catalyst surface, where the yield of LAO is dependent on the acid–base ratio of alumina [ 41 ]. Thus, an XPS analysis was carried out to obtain information on the oxidation states and element contents of the alumina catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The produced di-stearyl ether intermediate can be decomposed into α-olefin and water (d). Here, the α-olefin formation pathways require an acid–base pair consisting of Al and surface O (or OH) [ 41 ]. The isomerization of α-olefin to iso-olefin (linear internal olefin, LIO) (c) can take place through re-adsorption of α-olefin on LAS on the surface of alumina [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…They improved the selectivity further to 95% with almost full conversion at 400 °C by introducing a barium impregnation of 2 wt % to the alumina catalyst . The selectivity improvement caused by Lewis basic sites was also investigated by Chen et al with sodium-impregnated Al 2 O 3 . Boronic acid and phosphoric acid impregnated in ZrO 2 and TiO 2 are among other catalysts used for the dehydration of octanol with temperatures around 350 °C. , Other groups have used, for example, ion-exchange resins or Amberlyst-70 for the dehydration of octanol but with a selectivity toward dioctylether rather than octenes, studying the equilibrium of the two competing reactions.…”
Section: Introductionmentioning
confidence: 99%